The Effect of Spatial Working Memory Deterioration on Strategic Visuomotor Learning across Aging - Luis A. Uresti-Cabrera; Rosalinda Diaz; Israel Vaca-Palomares; Juan Fernandez-Ruiz (Behavioural Neurology)
Objective. To evaluate the effect of age-related cognitive changes in a visuomotor learning task that depends on strategic control and contrast it with the effect in a task principally depending on visuomotor recalibration. Methods. Participants performed a ball throwing task while donning either a reversing dove prism or a displacement wedge prism, which mainly depend on strategic control or visuomotor recalibration, respectively. Visuomotor performance was then analysed in relation to rule acquisition and reversal, recognition memory, visual memory, spatial planning, and spatial working memory with tasks from the Cambridge Neuropsychological Test Automated Battery (CANTAB). Results. The results confirmed previous works showing a detrimental effect of age on visuomotor learning. The analyses of the cognitive changes observed across age showed that both strategic control and visuomotor recalibration had significant negative correlations only with the number of errors in the spatial working memory task. However, when the effect of aging was controlled, the only significant correlation remaining was between the reversal adaptation magnitude and spatial working memory. Discussion. These results suggest that spatial working memory decline across aging could contribute to age-dependent deterioration in both visuomotor learning processes. However, spatial working memory integrity seems to affect strategic learning decline even after controlling for aging.